Effect of goal discrepancy rumination on overgeneral memory - Lanning, Laura Ellen Rose (University of Exeter, 2015)
Objective: This study aimed to test predictions made by the self-memory system (SMS) model (Conway & Pleydell-Pearce, 2000), extensions of Williams et al.’s (2007) “capture and rumination” (CaR) mechanism (Debeer, Hermans, & Raes, 2009) and control theories of rumination (Martin & Tesser, 1996, 2006) in a non-clinical sample to further understand the processes underlying overgeneral memory (OGM). It was hypothesised that (i) ruminating on unresolved goals, compared to thinking about resolved goals, would increase OGM, in participants reporting high levels of trait brooding and (ii) that this effect would be greater following goal-cues that are derived from goal cues rated as (a) more important compared to those rated as less important; (b) more progress-discrepant compared to those rated as less progress-discrepant; (c) more relevant to unresolved goals compared to those that are rated as less relevant to unresolved goals. Method: A between-subjects factor of condition (resolved versus unresolved goal-focus induction) and a within-subjects factor of time (pre- and post-manipulation Minimal Instruction Autobiographical Memory Test [MI-AMT; Debeer et al., 2009]) design was utilised with 75 undergraduate and three masters psychology students (86.3 % female [n = 65]; age, M = 20.2 years, range = 18-43, SD = 4.9) from the University of Exeter. The MI-AMT was used to measure autobiographical memory (AM) specificity before and following a manipulation whereby participants were randomly assigned to either a control condition in which participants focussed on a resolved goal or an experimental condition which was designed to induce rumination about an unresolved (i.e., self-discrepant) goal. MI-AMT cues were adjectives relating to nomothetic goal-statements. Results: Hierarchical multiple regression analyses found neither an overall effect of condition nor an interaction between condition and brooding on AM specificity. Thus, induced rumination over unresolved goals did not lead to higher levels of OGM than induced focus on resolved goals amongst individuals high in trait brooding. Multilevel hierarchical regression found that the extent to which people high on brooding were less specific in the unresolved condition did not depend on the importance or progress-discrepancy ratings of the goal-statements from which the MI-AMT cues were developed, nor on the relevance of the goal-cues to the concern identified in the goal cueing task. Goal-cue relevance ratings showed a significant main effect on AM specificity qualified by an interaction with condition whereby participants reported decreasingly specific AMs in response to cues related to the concern after the resolved goal manipulation. Conclusion: These null findings suggest that rumination over unresolved goals may not increase OGM amongst non-clinical samples. A replication of this study should utilise state rumination checks to ensure that the goal cueing task successfully differentially induced state rumination between conditions. Further exploration of the role of reflection might elucidate which qualities of rumination are positively associated with OGM but not present in rumination about unresolved goals. Given that Williams et al.’s CaR mechanism was constructed to understand OGM in clinical depression, a replication of this study using a clinical sample may be a useful next step in testing predictions made by this theory.